Petrography and hydric characterization of the quarry material of the varieties of Borriol Stone (Castellón) - Ovejero, M.; Queralt, I.; de la Fuente, C. (Materiales de Construcción, 2005)
Borriol stone is one of the most widely used and well-known building materials in the Spanish province of Castellapn. It is a cretaceous limestone quarried in the El Abeller quarry, Borriol (Castellón). Since the seventeenth century it has been used in several historic buildings to be found both in the city of Castellaon and in nearby Valencia. Although it is commercially classified as a single rock type, two different lithologies or varieties can be distinguished in the Abeller outcrop; these represent vertical changes in the outcrop series andaré referred to in this paper as Ochre Borriol and Red Borriol. Petrographic, mineralogical and chemical studies were carried out, along with color determination. The stone s hydric parameters were obtained via the following tests: vacuum water absorption, free water absorption, desorption and capillary water absorption. Red Borriol is a reddish dolomitic grainstone with textures of dedolimitization. It is a low-porosity rock consisting mainly of calcite and dolomite, with quartz, illite, goethite and hematite as secondary minerals. As it has a low absorption coefficient, low capillarity index and rapid water desorption, it is expected to behave well under the action of weathering agents. Ochre Borriol is a yellowish packstonegrainstone with higher porosity. It is famed mainly of calcite and has less dolomite content than Red Borriol. Its accesory minerals are quartz, illite and goethite. It has a higher absorption coefficient and higher capillarity. Although it absorbs water more rapidly, its desorption is slower. As the hydric behavior of Ochre Borriol is less favorable, it is to be expected that its deterioration processes are encouraged by water circulation more than Red Borriol´sare.